A NEW GENUS OF TREMATODES FROM MARINE FISH - CABALLERO Y C, EDUARDO; C, EDUARDO (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1946)
Paragonimus rudis* was obtained from the lungs of Didelphis m mesamericana, and Mephitis ma macroura The author considers this sp synonymous to P westermani, P kellicotti, P ringeri and others In addition, Rhopalias coronatus, R horridus* and R
ANS INST BIOL
Keywords: NEW GENUS, TREMATODES, MARINE FISH; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; ZOOLOGIA MARINA